A Systematic Review of Physical Activity Interventions in Hispanic Adults - Melinda J. Ickes (Journal of Environmental and Public Health, 2012)
Healthy People 2020 aims to achieve health equity, eliminate disparities, and improve the health of all groups. Regular physical activity (PA) improves overall health and fitness and has the capability to reduce risk for chronic diseases. Identifying barriers which relate to the Hispanic population is important when designing PA interventions. Therefore, the purpose was to review existing PA interventions targeting Hispanic adults published between 1988 and 2011. This paper was limited to interventions which included more than 35% Hispanic adults (n=20). Most of the interventions were community based (n=16), although clinical, family-based, and faith-based settings were also represented. Interventions incorporated theory (n=16), with social cognitive theory and transtheoretical model being used most frequently. Social support was integral, building on the assumption that it is a strong motivator of PA. Each of the interventions reported success related to PA, social support, and/or BMI. Lessons learned should be incorporated into future interventions.